Implications of sexual reproduction of Tithonia diversifolia for implementing intensive silvopastoral systems - Santos-Gally, Rocío (Cuban Journal of Agricultural Science, 2023)
Conventional cattle breeding, from pasture to free-range, is one of the primary contributors to global environmental problems, including deforestation, climate change, and biodiversity loss, thereby representing an unsustainable production form. As a response, intensive silvopastoral systems combining purposely cattle and different plant strata (pastures, grasses, shrubs, palms and/or trees) have increased in Latin America. These systems increase forage supply and soil quality, promote greater diversity in organisms, and enhance animal welfare, which involves a sustainable agricultural practice. The use of Tithonia diversifolia as forage shrub represents a source rich in proteins and phosphorus for cattle. Its use raises incomes, due to higher productivity. The spread of T. diversifolia has been conducted primarily in a vegetative form, which translates into higher implementation costs, genetic variability reduction, and plants of feebler and more superficial roots. Seed sowing could optimize its use in intensive silvopastoral systems, being crucial to identify this species reproductive condition. Likewise, getting to know fruit heteromorphism variability (two forms in the individual) at population level may provide standards for the correct planning of seed collections. This study compiles outcomes on sexual reproduction and fruit heteromorphism in T. diversifolia, permitting to gain knowledge on the plant and its effect on the implementation of intensive silvopastoral systems.